'It's just a comic' - Or is it? Addressing the past in Rutu Modan's The Property. Issue 5 (20th October 2022) - Kohn, Ayelet; Weissbrod, RACHEL
Abstract : In this paper, we study Rutu Modan's graphic novel, The Property ( Ha-Nekhes in Hebrew), as a work which engages in a double exploration. First, we show how the story of Mica and her grandmother, who travel to Poland to reclaim a property lost in the Holocaust, is used by Modan to reflect on her medium and the artistic means it offers such as colour, speech balloons and onomatopoeic icons. Second, we analyse her self-conscious use of the toolkit of the comics artist to reflect on the past and its impact on the present. We investigate her conception of the past as a multilayered story, which consists of several individual stories that complement but also contest with each other, insinuating that there is no one authoritative version of the past. Finally, we argue that beyond the individual stories there are emotionally and politically charged national conflicts, which Modan evokes without referring to them directly. Our analysis sheds light on both the uniqueness of her work and the way it relates to other media texts which deal with similar topics.